2018
DOI: 10.1002/adtp.201800087
|View full text |Cite
|
Sign up to set email alerts
|

Organoids for Advanced Therapeutics and Disease Models

Abstract: Organoid culture is a fast-emerging technology in the biological and biomedical research fields, garnering interest due to its unique features of self-organization from diverse types of stem cells and close resemblance to organs in the human body. This innovative in vitro model system presents the possibility of significant advances in the understanding of human development and disease mechanisms as well as in the discovery of novel diagnostics and therapeutics. Here, the authors review several types of tissue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 187 publications
(246 reference statements)
0
25
1
Order By: Relevance
“…These findings indicated that the intestinal organoid system recapitulated the regenerative effects of MSC‐CM on the native intestinal epithelium after radiation. However, although most studies have reported that MSCs prevent intestinal damage in mouse models of radiation injury (Chang et al, 2013; Chen et al, 2015; Gao et al, 2012; S. Kim et al, 2019; Saha et al, 2011), MSC‐CM could not mitigate the viability of organoids on Day 3 after irradiation under the conditions used in this study. Furthermore, we also did not observe the protective effects of Wnt signaling activation on irradiated organoids (data not shown), as has been previously reported (Thotala, Geng, Dickey, Hallahan, & Yazlovitskaya, 2010).…”
Section: Discussioncontrasting
confidence: 53%
See 1 more Smart Citation
“…These findings indicated that the intestinal organoid system recapitulated the regenerative effects of MSC‐CM on the native intestinal epithelium after radiation. However, although most studies have reported that MSCs prevent intestinal damage in mouse models of radiation injury (Chang et al, 2013; Chen et al, 2015; Gao et al, 2012; S. Kim et al, 2019; Saha et al, 2011), MSC‐CM could not mitigate the viability of organoids on Day 3 after irradiation under the conditions used in this study. Furthermore, we also did not observe the protective effects of Wnt signaling activation on irradiated organoids (data not shown), as has been previously reported (Thotala, Geng, Dickey, Hallahan, & Yazlovitskaya, 2010).…”
Section: Discussioncontrasting
confidence: 53%
“…In fact, this system has shown to better retain in vivo characteristics than cell models and may be useful for applications in studies of normal digestive physiology, host–pathogen interactions, regenerative medicine by transplantation, and drug absorption/toxicity (Holloway, Capeling, & Spence, 2019; Yui et al, 2012; Zachos et al, 2016). To expand on these potential applications, many researchers are currently attempting to adapt organoid culture using a variety of methods, such as 3D bioprinting, coculture, and biomaterials (Holloway et al, 2019; S. Kim, Cho, Min, Kim, & Cho, 2019). However, further studies are needed to elucidate whether intestinal organoid responses to stress are relevant to the native intestinal epithelium.…”
Section: Introductionmentioning
confidence: 99%
“…492 Although it is doubtful that organoids will completely replace animal studies, we should evaluate the obvious advantages of using organoids in biocompatibility tests. 493 As Bredeboord et al 494 stated: ''We suggest that the use of organoids is complementary to, rather than in competition with, these classical research methodologies''. 494 In silico bioinformatics are computational frameworks, which are currently playing a key role in the discovery and validation of new chemical identities.…”
Section: State-of-the-art Of Evaluation Of Biological Responses and Fmentioning
confidence: 99%
“…In the past 50 years, clinical practice has been going through a transition fueled by technological developments. Biomed ical engineering, [1][2][3][4][5][6][7][8][9] material science, [10][11][12][13][14][15][16][17][18] and artificial intel ligence (AI) [19][20][21][22][23][24] have been transforming the entire medical landscape: diagnostics, [25][26][27][28][29][30][31][32][33] drug development, 24,[34][35][36] drug delivery, [37][38][39][40][41][42][43][44][45][46] and data analytics. [47][48][49]…”
Section: Introductionmentioning
confidence: 99%